An evaluation of the dose-response relationship in naturalistic treatment settings using survival analysis. - Hansen, Nathan B; Lambert, Michael J (Mental health services research, 2003)
To date, few studies have been published on the dose-response relationship in psychotherapy. The current study addresses limitations of previous research by using (1) clinical significance methodology to address the meaningfulness of patient change, (2) survival analysis to assess change across time, (3) assessment of patient change on a session-by-session basis, and (4) a large data set representing a variety of treatment settings. A total of 4,761 patients representing standard treatment settings in the United States were tracked at each session of therapy. A survival analysis of this data reveals that between 15 and 19 sessions of therapy are required for a 50% recovery rate using clinical significance methodology. The results of this study provide a useful overview of time-to-change in naturalistic settings that can be used to estimate reliable treatment expectations and as a baseline for comparison when modifications are made within treatment delivery systems.
Keywords: Adult; Community Mental Health Centers; Health Maintenance Organizations; Health Services Research; Humans; Mental Disorders; Middle Aged; Occupational Health Services; Proportional Hazards Models; Psychotherapy; Questionnaires; Self Efficacy; Sickness Impact Profile; Survival Analysis; Time Factors; Treatment Outcome; United States